2016
DOI: 10.1002/jnr.23963
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences, gender and addiction

Abstract: This review discusses alcohol/other drug addiction as both a sociocultural and biological phenomenon. Sex differences and gender are not solely determined by biology, nor are they entirely sociocultural. The interactions among biological, environmental, sociocultural and developmental influences result in phenotypes that may be more masculine or more feminine. These gender-related sex differences in the brain can influence the responses to drugs of abuse, progressive changes in the brain after exposure to drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
329
5
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(372 citation statements)
references
References 119 publications
17
329
5
4
Order By: Relevance
“…The gender is socially constructed as identity. This identity is a socially influenced role that, whether male or female, is shaped by traditional, cultural structures, and social ideas 911. Because of the dynamic nature of the modern discussion about the terms “sex” and “gender,” we hereby follow the definition for the term “gender,” which is used of a global institution, the WHO 12,13…”
Section: Discussionmentioning
confidence: 99%
“…The gender is socially constructed as identity. This identity is a socially influenced role that, whether male or female, is shaped by traditional, cultural structures, and social ideas 911. Because of the dynamic nature of the modern discussion about the terms “sex” and “gender,” we hereby follow the definition for the term “gender,” which is used of a global institution, the WHO 12,13…”
Section: Discussionmentioning
confidence: 99%
“…The pioneer studies revealed that males exhibit greater symptoms of withdrawal compared to females (Becker et al, 2017[11]). Moreover, males have a longer period of abstinence, and females are more likely to relapse compared to males (Becker et al, 2017[11]). Furthermore, ovarian hormones influence the drug taking in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of the hormone level during the estrous cycle might enhance the initial reinforcement effect that the lad females get from drugs abuse. However, once the addictive behavior was established, the hormone does not play a role (Becker et al, 2017[11]). Moreover, females exhibit higher reinstatement in drugs and morphine seeking compared to the males (Anker and Carroll, 2010[6]; Feltenstein et al, 2011[25]; Becker and Koob, 2016[10]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations